Evaluation of Medical Educator Training Program at the University of Public Health, Myanmar - Ye Aung; Aung Kyaw; Khin Myint; Khaing Mon; Ei U; Pai Thitsar; Lay Myint; Nwe Myint; Tin Tun (Higher Education Research, 2026)
Faculty development in medical education has become essential for strengthening the teaching capacity of health professionals worldwide. In low- and middle-income countries (LMICs) such as Myanmar, there remain challenges in adequately preparing educators to meet modern curricular demands. To address this, the University of Public Health (UPH), Myanmar, has conducted a structured Medical Educator Training Program since 2003. However, evidence of its effectiveness is limited. A convergent mixed-methods study was conducted among participants enrolled in the 2025 Medical Educator Training Program at the University of Public Health, Myanmar. Kirkpatrick’s Levels 1 (Reaction) and 2 (Learning) frameworks guided the evaluation. Quantitative data were collected using structured questionnaires, while qualitative data were obtained from participants’ reflective reports. Descriptive statistics and thematic analysis were employed. Participants reported high levels of satisfaction with the program and perceived improvements in educational knowledge, teaching skills, curriculum development, learner assessment, leadership, professionalism, communication, and educational research competencies. Qualitative findings revealed transformative changes in educational perspectives, enhanced reflective practice, strengthened professional identity, and increased confidence in educational leadership roles. The Medical Educator Training Program was effective in improving participants’ educational competencies and professional development. Continued investment in faculty development programs may contribute to strengthening medical education quality and health professions education capacity in Myanmar.